Electrical transport analysis of Cr³⁺ substitution at the Mn-site site of divalent-doped La₀.₅Ca₀.₅Mn1-xCrₓO₃ (x = 0, 0.03, 0.05) manganite using scattering and hopping models - Zulkifli, Mohammad Aidil Ikhwan (2025)
The study focusses on Cr3+ substitution at the Mn-site of divalent-doped La₀.₅Ca₀.₅Mn1-xCrₓO₃ (x = 0, 0.03, 0.05) on the electrical transport properties. The samples were successfully synthesised by the conventional solid-state reaction method. The resistivity behaviour over a wide temperature range was studied. The electron transport mechanism in metallic region (T<TMI) was analysed using scattering model. The experimental data in the metallic region is best fitted with the scattering models ρ=ρ0+ ρ2T2+ρ4.5T4.5 suggested scattering involving grain boundary, electron-electron, and electron-magnon interaction. The fitted value of the parameter was observed to be decrease upon increasing Cr3+ content. The resistivity in metallic area was observed to be lower at higher Cr3+ substitutions and this may be attributed to the formation of double exchange interaction of Mn3+-O-Cr3+ and Mn3+-O-Mn4+. The resistivity behaviour in the metallic region was dominated by the domain or grain boundary resistivity. In insulating region (T>TMI), the small polaron hopping model with equation ρ(T)=BT e EaKBT was used to analyse the electron transport mechanism. The findings show that the presence of Cr3+ substitution enhances the activation energy resulted from enhanced Jahn-Teller lattice distortion, causes the polarons to localise. The combined findings show the complex competition between structural and electrical parameters in Cr-substituted manganites. These findings contribute to a deeper understanding of the transport phenomena in substituted manganite and their potential in electronic and spintronic applications.